Hydrogeochemical characterization of the Sakatti mine prospecting area, Sodankylä, Finnish Lapland - Lahtinen, Tatu (Helsingin yliopisto, 2017)
In 2011, Anglo American Sakatti Mining Oy published an ore discovery in Sodankylä, Finnish Lapland. The rich Ni-Cu-PGE orebody, named Sakatti ore, is partially underlying Viiankiaapa-mire’s Natura 2000 protection area. This sets additional challenges for the utilization of the resource without compromising the fragile nature of the area. To estimate the impacts of possible future mining operations, the complex hydrochemical and hydrogeochemical conditions at Viiankiaapa must be well understood. Most water samples from the research area show a chemical composition close to the natural Finnish groundwater composition Ca–HCO3. However, in four groundwater observation wells, located south from Kiimakuusikko, Na–HCO3 type waters were detected. These sites were GA300 (8.26 ppm of Na), GA202 (17.34 ppm of Na), GA202 deep (15.23 ppm of Na) and GA201 (7.92 ppm of Na). Source for the anomaly is likely lithological due to lack of chloride in the samples. One possible source could be weathering of albite to kaolinite. Albite is hosted in the breccia unit, located close to the site. Albite-kaolinite weathering could release Na+ ions into the surrounding soil solution, which would provide a source for the high sodium concentrations. Kitinen river shows slightly higher Al, Li and Cu contents compared to other waters from the research area. This could possibly be used to distinguish river water from groundwater at sites where river water infiltrates the groundwater system. On the other side, Na, K and DSi have higher concentrations in groundwaters compared to surface waters. This could make them useful groundwater indicators. Sakattioja and the other smaller streams draining the mire, are characterized by very high isotope values, low amounts of DSi and low EC. These characteristics likely reflect the hydrogeochemistry of the water on the surface of the mire. The hydrogeochemical similarity of these streams is also highlighted by the hierarchical cluster analysis, where the samples from these sites form a clear cluster of their ...